(untitled) (Proceedings of the International Conference on Public Health, 2017)
Adolescent period is the age of physical, emotional and social change. In participated adolescents with HIV, their lives are dealing with uncertainty and require specific health care management. This study was to examine health care needs, and health care service needs among 26 adolescents with HIV aged 10 – 20- years – old. Fifteen caregivers, nine health care providers and two representatives from private foundation agent were assessed for health care needs, and health care service needs for adolescent with HIV. Quantitative and qualitative approaches were used to collect data in adolescents living with HIV at a provincial hospital, Northeast of Thailand between March 2016 and March 2017. The quantitative data analysis entailed descriptive statistics with percentage, mean, and standard deviation while the qualitative data involved content analysis from individual cases, in-depth interviews, and focus group discussions. Findings demonstrated that adolescents with HIV has several needs such as (1) mental health care i.e. personal goal setting (2) sexual health care and prevention of transmission (3) life skill development and (4) non – disclosure health service. Nurses should help adolescents with HIV to meet essential needs in order to be satisfied on living with HIV.